2008
DOI: 10.1590/s0103-90162008000500013
|View full text |Cite
|
Sign up to set email alerts
|

Soil acidity, liming and soybean performance under no-till

Abstract: The effects of soil chemical changes on soybean root growth, mineral nutrition and grain yield, as a result of surface application of lime under no-till (NT), are still under discussion. A field trial was carried out on a loamy dystrophic Typic Hapludox at Ponta Grossa, Paraná State, Brazil, using a completely randomized block design with three replicates, in a split-plot experiment. The main plots received four dolomitic lime rates applied on the surface (0, 2, 4, and 6 Mg ha 3+ trocável e a saturação por alu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…Assim, nesse sistema de manejo, a efi ciência da calagem e a neutralização da acidez nas camadas mais profundas do solo podem diminuir, sendo os seus efeitos observados nas camadas mais superfi ciais do solo, como até os primeiros 10cm (LEAL et al, 2008;CORRÊA et al,2008, GONÇALVES et al, 2011. Apesar de os calcários serem poucos solúveis e os produtos de sua reação com o solo terem mobilidade limitada, há resultados experimentais que confi rmam a efi ciência da calagem superfi cial na correção da acidez de camadas superfi ciais e do subsolo em SSD (CAIRES et al, 2000;CAIRES et al, 2008).…”
Section: Introductionunclassified
“…Assim, nesse sistema de manejo, a efi ciência da calagem e a neutralização da acidez nas camadas mais profundas do solo podem diminuir, sendo os seus efeitos observados nas camadas mais superfi ciais do solo, como até os primeiros 10cm (LEAL et al, 2008;CORRÊA et al,2008, GONÇALVES et al, 2011. Apesar de os calcários serem poucos solúveis e os produtos de sua reação com o solo terem mobilidade limitada, há resultados experimentais que confi rmam a efi ciência da calagem superfi cial na correção da acidez de camadas superfi ciais e do subsolo em SSD (CAIRES et al, 2000;CAIRES et al, 2008).…”
Section: Introductionunclassified
“…Caires et al (2008) evaluated the behavior of soybean in acidic soils, noting that the decrease in exchangeable Al 3+ in soil after liming does not change the concentration of Al 3+ in roots and soybean leaves. In general, the production of soybean grains is not influenced by liming due to the low toxicity of aluminum and because acidic soils stimulated root growth.…”
Section: Phmentioning
confidence: 99%
“…The results indicated that liming with very high Al saturation had an important role in increasing soybean yield on tidal land, and maximizing yield required high rate of lime. Lime has been known as effective ameliorant to reduce soil acidity, decrease exchangeable Al as well as Al saturation (Caires et al, 2008;Sadiq and Babagana, 2012;Chimdi et al, 2012).…”
Section: Effect Of Lime Application On Soybean Growth and Yieldmentioning
confidence: 99%
“…Therefore, acidic subsoil could be effectively improved by incorporating the lime into subsoil. Some researchers showed that thelime incorporation in sub soils increased soil pH, decreased of Al-exchangeable and Al saturation and increased growth and yield of crops (de Oliveira and Pavan, 1996;Caires et al, 2008;Nora et al, 2014). It should be informed that the mobility of lime on acidic soil depended on the amount and time of lime application, soil type, soil pH, fertilizer management, climate and crop cultivation (Gascho and Parker, 2001;Conyers et al, 2003;Ernani et al, 2004;Caires et al, 2005).…”
Section: Effect Of Lime Application On Soybean Growth and Yieldmentioning
confidence: 99%